Considerations towards a roadmap for collection, handling and storage of blood extracellular vesicles. Issue 1 (1st December 2019) - Clayton, Aled; Boilard, Eric; Buzas, Edit I; Cheng, Lesley; Falcón-Perez, Juan Manual; Gardiner, Chris; Gustafson, Dakota; Gualerzi, Alice; Hendrix, An; Hoffman, Andrew; Jones, Jennifer; Lässer, Cecilia; et al.
ABSTRACT: There is an increasing interest in exploring clinically relevant information that is present in body fluids, and extracellular vesicles (EVs) are intrinsic components of body fluids ("liquid biopsies"). In this report, we will focus on blood. Blood contains not only EVs but also cells, and non-EV particles including lipoproteins. Due to the high concentration of soluble proteins and lipoproteins, blood, plasma and serum have a high viscosity and density, which hampers the concentration, isolation and detection of EVs. Because most if not all studies on EVs are single-centre studies, their clinical relevance remains limited. Therefore, there is an urgent need to improve standardization and reproducibility of EV research. As a first step, the International Society on Extracellular Vesicles organized a biomarker workshop in Birmingham (UK) in November 2017, and during that workshop several working groups were created to focus on a particular body fluid. This report is the first output of the blood EV work group and is based on responses by work group members to a questionnaire in order to discover the contours of a roadmap. From the answers it is clear that most respondents are in favour of evidence-based research, education, quality control procedures, and physical models to improve our understanding and comparison of concentration, isolation and detection methods. Since blood is such a complex body fluid, we assume that the outcome of the survey may also be valuable for exploring body fluids other than blood.